2019
DOI: 10.31629/anugerah.v1i1.1580
|View full text |Cite
|
Sign up to set email alerts
|

Desain Pembelajaran Berbasis Literasi Sains dan Berwawasan Kemaritiman sebagai Hasil Pelatihan di SMAN 4 Tanjungpinang

Abstract: Learning designing becomes an important part of the process to achieve learning objectives. Likewise, when teachers enhancestudents’ scientific literacy, the efforts must also be made from the learning design. The design of learning based on scientific literacy becomes very important when the orientation of science learning is not just to achieve cognitive aspects, but even more to the students' ability to apply science and have the attitude and ability to make decisions related to science in their lives. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, some science teachers (45%) have integrated the maritime context into their learning such as by presenting a discussion of the biotic and abiotic components of marine ecosystems, marine pollution and its prevention efforts, biodiversity in coastal areas and coral reefs, the application of Archimedes' law on ships, and tsunami disaster mitigation. The materials in science learning are combined with maritime context to ensure that teachers and students have knowledge and competence in protecting the marine environment [10]- [12], [18]. In addition, the understanding of maritime context needs to be given to science teachers for it to be integrated in the learning process, specifically in learning media [18], [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some science teachers (45%) have integrated the maritime context into their learning such as by presenting a discussion of the biotic and abiotic components of marine ecosystems, marine pollution and its prevention efforts, biodiversity in coastal areas and coral reefs, the application of Archimedes' law on ships, and tsunami disaster mitigation. The materials in science learning are combined with maritime context to ensure that teachers and students have knowledge and competence in protecting the marine environment [10]- [12], [18]. In addition, the understanding of maritime context needs to be given to science teachers for it to be integrated in the learning process, specifically in learning media [18], [19].…”
Section: Resultsmentioning
confidence: 99%
“…Science learning that is integrated with the maritime context is needed, specifically in coastal areas to support the realization of Indonesia as the world's maritime axis [13] and the learning process contextually [12]. However, research revealed that the context has not been widely practiced by teachers [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Melalui diskusi, siswa dapat saling berbagi pemahaman mereka tentang konsep vektor, memperluas pengetahuan mereka, dan membangun keterampilan berpikir kritis; 5] Memanfaatkan Teknologi dan Media: Desain tugas yang menggunakan teknologi dan media dapat memperkaya literasi sains siswa. Misalnya, memberikan tugas yang melibatkan pemodelan vektor menggunakan perangkat lunak simulasi atau meminta siswa untuk membuat presentasi multimedia tentang konsep vektor (Amelia & Yulita, 2019).…”
Section: Literasi Sainsunclassified
“…Finnaly, Lack of Guidance in Developing Science Literacy Movement. Based on the results of interviews, principals felt that there was a lack of guidance for schools, committees and teachers on how to implement and technical guidelines for the science literacy movement (Amelia & Yulita, 2019;Syofyan et al, 2018). So far, coaching has only come from the school supervisor.…”
Section: The Obstacles Faced By Schools In Implementing the Science L...mentioning
confidence: 99%